The exotic palm Roystonea oleracea (Jacq.) O. F. cook as a rural biotype for Rhodnius neglectus Lent, 1954, in Caçu, state of Goiás - Vianna, Elisa Neves (2014)
IntroductionRhodnius neglectus is a triatomine that colonizes different palm species. In this study, we aimed to describe the presence of this triatomine bug in the royal palms (Roystonea oleracea) in a rural region of the State of Goiás.MethodsPalm infestation was investigated by dissecting the palms or by using live-bait traps.ResultsTwo palm trees were infested by R. neglectusnegative for Trypanosoma cruzi, the etiological agent for Chagas disease. In the study area, R. neglectus is frequently found in households.ConclusionsThe adaptation of this species to palm trees introduced in Brazil for landscaping purposes poses another challenge for controlling the vectors of Chagas disease.